Justice and the cost of doing business: The Philippines - Maria Lourdes A. Sereno; Emmanuel S. de Dios; Joseph J. Capuno (University of the Philippines, School of Economics (UPSE), 2007)
The effect of the performance of the judicial system has been thrown into the limelight as the business sector has in various surveys pointed to its performance as being one of the main obstacles and disincentives to doing business in the Philippines. The channels through which judicial decisions may affect business behaviour are fairly straightforward and may be reduced to two: increased uncertainty and high costs. In order to quantify the perceived effect of the workings of the judiciary on the various economic decisions and on investment in general, a survey of 320 of the top 7000 corporations in the Philippines was conducted in 2001. Our findings show that governance problems are at least as important as economic or financial problems in doing business. Only weak market demand was cited as being more important than corruption, high crime levels, and lack of trust in government laws and policies as important obstacles to doing business. Of more direct relevance to the judiciary, difficulties in settling legal conflicts were the sixth most frequently cited factor affecting business, after high power costs but even more important than poor physical infrastructure and access to credit. Further, the current level of functioning of the legal system has an economic impact equivalent to foregoing at least 6-11 percent of total investment in the economy and foregoing at least one-fourth to onehalf of a percentage point (0.25-0.46) of GDP growth annually, or an annual loss amounting to between P7 billion and P13 billion in 1999 alone. These are significant and recurring economic losses attributable to the nature and functioning of institutions and form a strong case for judicial reform.
Keywords: 330; Rechtsordnung; Makroökonomischer Einfluss; Wirtschaftsordnung; Schätzung; Philippinen